Yield-related traits and proximate content of winged bean for seed production purpose - SAYYIDAH AFRIDATUL ISHTHIFAIYYAH; MUHAMAD SYUKUR; TRIKOESOEMANINGTYAS TRIKOESOEMANINGTYAS; AWANG MAHARIJAYA; SITI MARWIYAH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Ishthifaiyyah SA, Syukur M, Trikoesoemaningtyas, Maharijaya A, Marwiyah S. 2023. Yield-related traits and proximate content of winged bean for seed production purpose. Biodiversitas 24: 3609-3615. The winged bean is an underutilized plant that can produce valuable seeds with great nutrient content. Meanwhile, the lack of improved genotypes limits its large-scale cultivation. This study aimed to evaluate the flowering and maturity time of winged bean lines and elaborate on various traits correlated with the seed yield. We also performed the seeds' proximate analysis to unravel each line's nutrient content. This study was conducted in Bogor, Indonesia, between April and October 2020. Hybridization between two distinct parents had successfully developed early flowering winged bean genotypes in its progeny. The H4P and L3 had the highest seed yield (1.40 t ha-1) with brown and purple seed colors, respectively. The dried pod weight (0.56), young pod weight (0.36), and the number of dried pods (0.39) had a positive direct effect yet were still smaller than their correlation coefficient. Thus, the selection process to obtain high-yielding winged bean genotypes can be conducted simultaneously through those traits. The evaluated winged bean genotypes had various fat and protein content ranging from 11.10% to 16.48% and 28.81% to 33.45%, respectively. This information can be used as future selection criteria for the winged bean breeding program.